Portrait of Islamic Religious Education in Public Universities in the 5.0 Era - Bachrul Ulum; Mohammad Hasib; Moh. Zaini (Research Institute and Community Engagement of UIN MADURA, 2023)
In the 5.0 era, Islamic religious instruction in higher education is crucial as in forming students' morality and character. With a correct and deep understanding of religion, students can internalize these values in their daily lives and make good and responsible decisions. The article's aim is to give an outline of the Islamic religious teaching and learning processes in public colleges as of 5.0. A qualitative research methodology was adopted, and instructors and students were interviewed as well as observed to obtain data involved in the learning and teaching process of Islam in public universities. Then, content analysis is used to assess the acquired data utilizing qualitative data analysis techniques. The findings indicated that there is still room for improvement in the standard of Islamic religious instruction in public universities, especially in terms of subpar teaching and learning. Lack of emphasis on character education, poor teaching, and minimal use of technological in the process of learning and instruction are some of the reasons that contribute to the poor quality of Islamic religious education in public universities. Thus, character education, raising the bar of instruction, and implementing better technology in the learning and teaching process of Islam in the 5.0 era are necessary to improve the quality of Islamic religious instruction in public universities. (Di era 5.0, pengajaran agama Islam di perguruan tinggi menjadi sangat penting dalam membentuk moralitas dan karakter mahasiswa. Dengan pemahaman agama yang benar dan mendalam, mahasiswa dapat menginternalisasi nilai-nilai tersebut dalam kehidupan sehari-hari dan mengambil keputusan yang baik dan bertanggung jawab. Artikel ini bertujuan untuk memberikan gambaran umum tentang proses pengajaran dan pembelajaran agama Islam di perguruan tinggi umum di era 5.0. Metodologi penelitian kualitatif diadopsi, dan para pengajar serta mahasiswa diwawancarai serta diobservasi untuk mendapatkan data yang terlibat dalam proses belajar dan mengajar agama Islam di perguruan tinggi umum. Kemudian, analisis isi digunakan untuk menilai data yang diperoleh dengan menggunakan teknik analisis data kualitatif. Temuan penelitian menunjukkan bahwa masih ada ruang untuk perbaikan dalam standar pengajaran agama Islam di perguruan tinggi umum, terutama dalam hal pengajaran dan pembelajaran yang masih di bawah standar. Kurangnya penekanan pada pendidikan karakter, pengajaran yang buruk, dan minimnya penggunaan teknologi dalam proses belajar mengajar merupakan beberapa alasan yang berkontribusi terhadap rendahnya kualitas pendidikan agama Islam di universitas umum. Oleh karena itu, pendidikan karakter, peningkatan standar pengajaran, dan penerapan teknologi yang lebih baik dalam proses pembelajaran dan pengajaran agama Islam di era 5.0 sangat diperlukan untuk meningkatkan kualitas pengajaran agama Islam di perguruan tinggi umum.)